Relationship between Nutritional Screening Tools and GLIM in Complicated IBD Requiring Surgery - Camilla Fiorindi (MDPI AG, 2021)
Background: Accurate identification of malnutrition and preoperative nutritional care in Inflammatory Bowel Disease (IBD) surgery is mandatory. There is no validated nutritional screening tool for IBD patients. We developed a novel nutritional screening tool for IBD patients requiring surgery and compared it with other tools. Methods: we included 62 consecutive patients scheduled for elective surgery. The IBD Nutritional Screening tool (NS-IBD) was developed to screen patients for further comprehensive assessment. NRS-2002, MUST, MST, MIRT, SaskIBD-NR are compared with the new test. All screening tests were subsequently related to new GLIM criteria. Results: according to GLIM criteria, 25 (40%) IBD patients were malnourished (15 CD and 10 UC, 33% vs. 63%, p = 0.036). Stage 1 malnutrition was reported in ten patients, while stage 2 was detected in 15 patients. The comparison of each nutritional risk tool with GLIM criteria showed sensitivity of 0.52, 0.6, 0.6, 0.84, 0.84 and 0.92 for SASKIBD-NR, MUST, MST, NRS-2002, MIRT, and the new NS-IBD, respectively. Conclusions: in IBD, currently adopted nutritional screening tools are characterized by a low sensitivity when malnutrition diagnosis is performed with recent GLIM criteria. Our proposed tool to detect malnutrition performed the best in detecting patients that may require nutritional assessment and preoperative intervention.